Direct cyclopexy surgery for post-traumatic cyclodialysis with persistent hypotony: ultrasound biomicroscopic evaluation - Murta,Fabiola (2014)
Cyclodialysis is a relatively rare condition usually caused by ocular injury; however, it can also be caused iatrogenically during intraocular surgery. Hypotony maculopathy is the most important complication and the primary reason for visual loss. Clinical diagnosis using gonioscopy may be difficult, and ultrasound biomicroscopy (UBM) can be an alternative. There are different kinds of treatments, and the optimal one remains controversial. Here we describe a case of traumatic cyclodialysis with persistent ocular hypotony treated by direct cyclopexy, as illustrated by UBM performed before and after surgery.